Low back pain in elite rhythmic gymnasts - Hutchinson, M. R. (Medicine & Science in Sports & Exercise, 1999)
Methods: To document the presence and severity of low back pain in elite rhythmic gymnasts, a prospective study of seven national team members was undertaken that documented injuries and complaints with daily medical reports over a 7-wk period. These findings were correlated with a retrospective review of 11 elite level gymnasts followed over a 10-month period whose complaints ultimately required evaluation by a physician. Results: Eighty-six percent of the gymnasts in the prospective study complained of back pain at some point over the course of the study. The only injury recorded that required a time loss from sport was a low back injury. The most common complaint requiring a physician's evaluation was low back pain with the diagnoses varying from muscle strains to bony stress reaction or complete fracture of the pars inter-articularis (spondylolysis). No athlete had a spondylolisthesis or ruptured disk. Two had mild scolioses which did not appear to be associated with their low back pain. Conclusions: It would appear that rhythmic gymnasts are at relative increased risk of suffering low back complaints secondary to their sport.